Compostos bioativos antioxidantes de Maytenus ilicifolia Mart. ex Reissek inibem a peroxidação lipídica e oxidação da LDL e glicação do colágeno frente ao metilglioxal - Bittar, Vinicius Prado (2022)
Maytenus ilicifolia Mart. ex Reissek, better known by the popular names “Espinheira-santa”, “Cancerosa” or “Cancorosa” is commonly used in Brazil to treat gastrointestinal disorders. The main objective of this study was to analyze in vitro and ex vivo the ethanol extract of the maytenus ilicifolia leaf (EE-Mi) and its organic fractions hexane (FH-Mi), dichloromethane (FDM-Mi), ethyl acetate (FAE-Mi), n-butanol (FB-Mi) and hydromethane residue (FHM-Mi) and submit these samples for analysis of antioxidant capacity, antiglicant, enzymatic inhibition capacity, lipid peroxidation protection capacity and low density lipoprotein (LDL) oxidation protection capacity. In all experiments, the FAE-Mi and FB-Mi fractions showed the best results, from this conclusion, these fractions were primarily analyzed in HPLC-ESI-MS/MS, where it was possible to identify compounds with antioxidant capacity, capacity for enzymatic inhibition and inhibition of lipid peroxidation, such as: malic acid, catechin and catechin, quercetin and kaempferol derivatives. In the iron reduction capacity (FRAP) assay, all samples, with the exception of FHM-Mi, presented values between 752 ~ 953 μmol Trolox eq.eg-1, similar to the positive control quercetin (987 mmol Trolox eq.eg-1), in the peroxil radical sequestration method (ORAC), the fractions showed no statistical difference when compared with the positive control, quercetin (2279 μmol Trolox eq.eg-1) varying the values of 2332 ~2509 μmol Trolox eq.eg-1 and in the scavenger of the DPPH radical the samples were submitted to the EC50 calculation, where the sample with the best result was FAEMi (2.42 µg/mL). In all glycation models (BSA/fructose, BSA/methylglioxal, Arginine/methylglioxal and Collagen/methylglioxal), the samples presented antiglicant potential, with the exception of FHM-Mi. The FAE-Mi (25 μg/mL) and FB-Mi (46 μg/mL) fractions were able to inhibit 50% of collagen glycation against methylglioxal compared to positive control. The EE-Mi, FAE-Mi and FB-Mi samples showed enzymatic inhibitory activity of α-amylase, expressing low Values of EC50 (2.42, 7.95 and 23.83 μg/mL), compared with the positive control. In the ex vivo lipid peroxidation induction model, it was observed that EE-Mi (0.11 nmol MDA/mg Proteins), FAE-Mi (0.10 nmol MDA/mg Proteins), FB-Mi (0.09 n molmol MDA/mg Proteins) and quercetin (0.08 nmol MDA/mg Proteins) showed inhibitory capacity of lipid peroxidation compared to oxidized liver tissue (0.36 nmol MDA/mg Proteins). With the exception of the hydromethane fraction (FHM-Mi), all other fractions were effective in inhibiting LDL oxidation, where the results ranged from 0.76 to 3.45 in the calculation of the area under the curve (AUC) compared to oxidized LDL (15.27) and untreated LDL (1.30 AUC). All samples, with the exception of FHM-Mi, presented values above 50% of LDL glycation inhibition were able to protect LDL against lipid peroxidation (100% inhibition). The results obtained in this work are consistent with the medicinal capacity of the plant, since it has a high concentration of flavonoids, phenolic compounds and condensed tannins. In conclusion, the ethanolextract of Maytenus ilicifolia and its organic fractions presented a high biological potential, results that favor the continuation of the work in an in vivo model, to elucidate more specifically the mechanisms of action of Maytenus ilicifolia.